"Isolated Atrial Inversion" Without Transposition Physiology: Yet Another "Twisted Heart". (July 2014) - Gupta, Saurabh Kumar; Gulati, Gurpreet Singh; Saxena, Anita; Ho, Siew Yen; Juneja, Rajnish
Atrial inversion (or mirror-imaged atrial arrangement) occurring in isolation, that is, without corresponding mirror imagery of the viscera, has been previously shown with discordant atrioventricular connections resulting in transposition physiology. We hereby report a case of "isolated atrial inversion" wherein atrioventricular connections were concordant owing to the presence of criss-crossing of the ventricular inflows.